(untitled) (Sains Humanika, 2017)
The purpose of the study is to investigate the role of continuance commitment in the relationship between affective commitment and organizational citizenship behaviour (OCB) among the employees of telecommunication industry players in Mogadishu, Somalia. A total of 92 lower managers (supervisors) from three different telecommunication players were involved in this study. The instrument used in the study for affective and continuance commitment was adopted from Natalie J. Allen and John P. Meyer (1990), and for OCB was adopted from Philip M. Podsakoff , Scott B. MacKenzie, Robert H. Moorman, and Richard Fetter (1990). This quantitative survey method employed stratified random sampling technique. Employees’ attitudes and behaviours were tested for correlation and regression analysis. The findings indicated that there are positive and significant relationship between employees’ affective commitment, continuance commitment and OCB. The highest correlations towards employees’ citizenship behaviour is the mediation role of continuance commitment (r=.362, p< .05), then affective commitment (r=.287, p< .05), followed by the relationship between affective commitment and continuance commitment (r=.249, p< .05), whilst continuance commitment shows the weakest relationship on OCB (r=.144, p< .05). The regression model indicates a predictive significance by employees’ behaviours; thus, the findings support the conclusion that the selected behaviours are predictors of telecommunication industries employees’ OCB. This study revealed the importances of organizational citizenship behaviour (OCB), affective commitment and continuance commitment among the telecommunication industries employees’in Mogadishu, Somalia. These findings also have implications for telecommunication industries and managers to reflect and extend employees’ organizational citizenship behavior (OCB).